DOP23 Endoscopic evaluation at 1 month after ileocolic resection for Crohn's disease predicts postoperative recurrence and is safe. (15th January 2020) - Guo, Z; Zhu, Y; Cao, L; Li, Y; Wang, Z; Zhu, W
Abstract: Background: Endoscopic surveillance remains the gold standard for evaluating postoperative recurrence in Crohn' disease (CD). However, the optimal timing of the first postoperative endoscopic evaluation is unclear. The commonly used strategy, first endoscopy at 3, 6, or 12 months, demonstrates high rates of endoscopic recurrence, which means this strategy may delay the detection and treatment. The aim of this study was to determine the clinical value and safety of the endoscopy at 1 month after surgery, and define the related factors. Methods: This was a prospective cohort study of CD patients undergoing an ileocolic resection between 2015 and 2018, with a postoperative colonoscopy at 4–5 week after surgery. The primary outcome was endoscopic recurrence at 12 months, or clinical recurrence, or surgical recurrence within 12 months after surgery. Univariate and multivariate analyses were performed to identify related factors. Results: Eighty-four eligible CD patients were included. Among 84 colonoscopies at 4–5 week, no endoscopic complication occurred. The main endoscopic findings at the first evaluation were anastomotic ulcers (45 [10 circumferential ulcers and 35 scattered ulcers], 53.6%), ulcers in the neoterminal ileum (16, 19.0%), oedema in anastomosis (50, 59.5%), mild narrowing in anastomosis (7, 8.3%), and mild narrowing in neoterminal ileum (3, 3.6%). On univariate and multivariable analysis, anastomotic scattered ulcers were associated with forward postoperative recurrence (HR, 2.532; 95% CI, 1.019–6.318; p = 0.046). We then used the modified Rutgeerts score to define endoscopic findings: i0, 26(44.0%); i1, 4(4.8%); i2a (circumferential anastomotic ulcers were not included), 40(34.5%); i2b, 11(13.1%); i3, 0; i4, 3(7.1%). Univariate and multivariable analysis showed ≥i2a were associated with forward postoperative recurrence (HR, 3.174; 95% CI, 1.218–8.273; p = 0.018). No factor was associated with ≥i2a at the first endoscopy. Conclusion: Endoscopic evaluation at 4–5 weeks after surgery in CD was safe, and endoscopic findings were associated with postoperative recurrence. Earlier endoscopic examination after surgery may be useful for the adjustment of medication.